In Silico Analysis of Cucurbitacin IIa and Cucurbitacin IIb as Potential Modulators of Oxidative Stress Regulatory Proteins - Sarmoko, Sarmoko; Suprahman, Nisa Yulianti; Putri, Refsya Azanti; Hakim, Ahmad Zammi Autadan; Cahyadi, Dzaky Raihan; Saputra, Muhammad Yogi (Indonesian Journal of Cancer Chemoprevention, 2024)
Oxidative stress, resulting from imbalance between rective oxygen species (ROS) production and antioxidant defenses, contributes significantly to numerous pathological conditions, including inflammation, cancer and neurodegeneration. Natural compounds with antioxidant properties offer promising therapeutic potential. This study aims to investigate the potential of Cucurbitacin IIa and IIb to modulate oxidative stress regulatory proteins (NOS2, Lipoxygenase, KEAP1, and Xanthine oxidase) using molecular docking approaches. Target protein structures were retrieved from the RSCB Protein Data Bank. Ligand geometries were constructed and optimized using density functional theory. Molecular docking was performed using AutoDock 1.5.6 with a validated docking protocol (RPMS<2Å). Our results demonstrated favorable binding energies for both compounds with NOS2 (-9.75 and -9.57 kcal/mol) and KEAP1 (-8.52 and -9.34 kcal/mol), approaching the affinities of their respective native ligands. Moderate binding was observed with Lipoxygenase (-6.14 and -5.54 kcal/mol), while both compounds showed incompatibility with Xanthine oxidase, as evidenced by highly positive binding energies. The interaction between Cucurbitacins with NOS2, KEAP1 and Lipoxygenase was mediated through hydrogen and hydrophobic interaction. These findings provide mechanistic insight into their bioactivity and support further experimental studies for therapeutic development in oxidative stress-related disorders.Keywords: Cucurbitacin, Molecular docking, Oxidative stress, NOS2, KEAP1.